Sensing characteristics of dc reactive sputtered WO3 thin films as an NOx gas sensor - Kim, TS; Kim, YB; Yoo, KS; Sung, GS; Jung, HJ (ELSEVIER SCIENCE SA, 2000)
In order to apply WO3 thin films to the NOx gas sensor, WO3 thin films (3000 Angstrom) were fabricated by using de reactive sputtering method on alumina substrate and assembled as a unit of an NOx gas sensor by adopting a patterned heater on the brick side of substrate. The deposition temperatures of WO3 thin film were changed from 200 degrees C to 500 degrees C, and then post-annealed for the crystallization for 4 h at 600 degrees C. There were no WO3 phases at the substrate temperature of 200 degrees C, but the crystalline phases of WO3 thin film were appeared with the increase of substrate temperature from 200 degrees C to 500 degrees C, The post-annealing of as-deposited WO3 thin films at 600 degrees C resulted in the enhancements of crystallinity, but it was observed that the quality of the final phases severely depends on the initial formation of phase during deposition. From the SEM images, crack free morphologies were found, which was different from the room temperature growth films. The sensitivity (R-gas/R-air) of as-deposited thin films was ranged from 4 to 10 for the 5 ppm NO test gas at the measuring temperature of 200 degrees C, However, after post-annealing process at the temperature of 600 degrees C, the sensitivities were increased around the values of 70-180 at the same test condition. These results show the WO, thin films need to be processed at least at the temperature of 600 degrees C for the well-improved sensitivity against NOx gas. It was also observed that the recovery rate of a sensing signal after measuring sensitivity was faster in the in-situ sputtered films than in the evaporated films or room temperature sputtered films. (C) 2000 Elsevier Science S.A. All rights reserved.
Keywords: OXIDES